Circulating Tumor DNA as an Early Indicator of Response to T-Cell Transfer Immunotherapy in Metastatic Melanoma - Xi, Liqiang (Clin Cancer Res, 2016)
PURPOSE: Adoptive transfer of activated autologous tumor-infiltrating lymphocytes (TIL) can mediate complete, durable regressions in patients with metastatic melanoma (MM). Responding patients generally do not have significant changes in non-cutaneous RECIST targets before 30–60 days following TIL infusion, and complete responses are often not confirmed for 1–2 years. There is a critical need for a biomarker that can provide early information regarding the likelihood and duration of a response to enable rational decisions about altering therapy. We wished to evaluate the role of ctDNA in separating responding from non-responding patients. EXPERIMENTAL DESIGN: We studied BRAF V600E ctDNA levels by a sensitive allele specific PCR assay in 388 serum samples from 48 patients who received TIL immunotherapy at the National Cancer Institute, and correlated differences in the dynamic patterns of their ctDNA measurements with response outcomes. RESULTS: A strong correlation was found between the presence or absence of an early serum peak of V600E ctDNA, and the likelihood of an objective response. Furthermore, patients that developed an early ctDNA peak and cleared their serum of V600E ctDNA were highly likely to achieve a complete response over the next 1–2 years. Patients that showed no peak of V600E ctDNA failed to achieve an objective response, with one exception. CONCLUSION: We show that the dynamic changes occurring in BRAF V600E ctDNA levels within the first month following T-cell transfer immunotherapy in MM can be used to rapidly identify responding from non-responding patients, potentially allowing clinicians to make critical treatment-related decisions in a more timely manner. These data also suggest that the majority of tumor killing by TIL occurs very early after the initiation of therapy.